Gambaran fungsi penghidu dengan Sniffin’ sticks pada pasien rinitis alergi - Nurul Endah Ardianti; Nina Irawati; Niken Lestari Poerbonegoro; Saptawati Bardosono (PERHATI-KL, 2012)
Background: Allergic rhinitis (AR) is defined as an inflammation of the lining mucosa of the nose induced by allergen exposure. The olfactory disturbance could affect around 21%-23% of AR patients.Purpose: To determine the olfactory performance of AR patients at the Allergy-Immunology outpatientclinic, ENT Department, Cipto Mangunkusumo Hospital. To find out the mean difference of olfactorythreshold, discrimination, and identification (TDI) score between intermittent AR group and persistent ARgroup, and also to determine the percentage of the AR patient who had olfactory disturbance. Method:Observational descriptive study with cross sectional method to assess the TDI in AR patients using theSniffin’ sticks extended test. Results: The olfactory performance characteristics of AR patients were:threshold score 0,25; discrimination score 7,00; identification score 10,10; TDI score 23,50. There wasno statistical difference of the TDI mean score between intermittent AR group and persistent AR group.In our study, 45% of all AR subjects were reported to have olfactory disturbance. Conclusion: The TDIresults which represent olfactory function of AR patients were lower compared to the healthy subjects. Key words: allergic rhinitis, olfactory function, Sniffin’ sticks Abstrak : Latar belakang: Rinitis alergi (RA) adalah penyakit inflamasi mukosa hidung akibat pajanan terhadap suatu alergen. Sekitar 21% sampai 23% pasien RA dapat mengalami gangguan penghidu. Tujuan: Mengetahui gambaran fungsi penghidu pada pasien rinitis alergi (RA). Menentukan perbedaan rerata nilai ambang, diskriminasi dan identifikasi (ADI) pada pasien RA intermiten dan persisten, dan mengetahui persentase pasien RA dengan gangguan fungsi penghidu di poliklinik Divisi Alergi-Imunologi, Departemen THT RSCM. Metode: Penelitian observasional dengan metode potong lintang untuk menilai ADI penghidu pada percontoh RA menggunakan pemeriksaan Sniffin’ sticks extended test. Hasil: Didapati karakteristik fungsi penghidu percontoh RA ambang 0,25; diskriminasi 7,00; identifikasi 10,10; nilai ADI 23,50. Tidak didapatkan perbedaan bermakna rerata nilai ADI antara kelompok rinitis alergi persisten dan intermiten. Diperoleh 45% dari seluruh percontoh RA mengalami gangguan fungsi penghidu. Kesimpulan: Nilai ADI yang merupakan fungsi penghidu pasien RA lebih rendah dibandingkan dengan subjek sehat. Kata kunci: rinitis alergi, fungsi penghidu, Sniffin’ sticks